EFFECT OF CROSSLINKING AGENT ON DEVELOPMENT OF GASTRORETENTIVE MUCOADHESIVE MICROSPHERES OF RISEDRONATE SODIUMâ€ - Gedam, Shweta; Jadhav, Pritee; Talele, Swati; Jadhav, Anil (International Journal of Applied Pharmaceutics, 2018)
Objective: The present investigation was undertaken to develop and evaluate a gastroretentive mucoadhesive microspheres of anti-osteoporosis drug risedronate sodium to enhance the residence time and drug release by studying the effect of the crosslinking agent to obtain the best formulation with reduced particle size and good in vitro mucoadhesion strength. Methods: Selected drug risedronate sodium is a potent pyridinyl bisphosphonate used for the treatment of osteoporosis, and other bone disorders. Microspheres using sodium alginate as a polymer and calcium chloride solution as a cross-linker were prepared successfully by the emulsification crosslinking method. The 23 factorial design was used to study the effects of various variables like a drug: polymer ratio, crosslinking agent concentration and crosslinking time on the particle size and in vitro mucoadhesion strength. All these formulations were evaluated for entrapment efficiency, percentage yield and cumulative drug release. F1 batch was selected as best formulation and evaluated for scanning electron microscopy, fourier transforms infrared spectroscopy, differential scanning calorimetry, stability study. Results: Design batches were evaluated for percent yield (61.29-89.33%), % entrapment efficiency (42.25±0.620-62.58±0.330), mucoadhesion strength (68.15±0.37-82.24±0.72%) and drug release at 12 h (67-84%). Among the microspheres formulation, an F1 batch of (0.5:1) drug: polymer concentration and at 4% concentration of calcium chloride as a crosslinker was considered best formulation with reduced particle size 32.85±0.774μm, % intro mucoadhesion. 82.24±0.72. In vitro mucoadhesion strength was increased with the increasing crosslinking time from 5 min to 10 min. The fourier transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC) study showed no interaction between drug and polymer. X-ray diffraction (XRD) spectrum of microspheres indicates that drug particles are dispersed at the molecular level in the polymer matrices so no indication of the crystalline nature of the drug nature. Scanning electron microscopic (SEM) study showed that microspheres were spherical in shape with a smooth surface. F1 batch shows percentage cumulative drug release 84.07%. In vitro dissolution studies indicates that percent cumulative drug release from microspheres follows zero order kinetics plot which indicates controlled-release drug-delivery for 12 h which leads to control of plasma concentration. Conclusion: The results show that the formulation that contains (0.5:1) drug: polymer ratio, calcium chloride in 4% concentration and crosslinking time 10 min is the best one and can be utilized to formulate risedronate sodium mucoadhesive microspheres to enhance gastric residence time, improved patient compliance and reduction in the frequency of drug administration.